THE LEXICAL EQUIVALENCE VARIETY OF F-WORDS TRANSLATION INTO INDONESIAN : CORPUS-BASED TRANSLATION RESEARCH - Isra F. Sianipar; Sajarwa Sajarwa (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2022)
Translating the movie subtitle is increasingly recognised as a meaning-making mode and language variety in its own right. However, making the meaning is a difficult task when the word is considered taboo in the target language. Therefore, this study attempts to identify the translation of F-Words which are generally considered taboo in Indonesia. The object material of this study is corpus parallel, OpenSubtitle Corpus 2016 which contains correspondence of English- Indonesian data, and focuses on seeing the F-Words translation. The F-Words in this research consisted of fuck, fucks, fucking, fucked, fucker and its compounds such as motherfucker, motherfuck, and motherfucking. This present study employed translational research which took an interpretative qualitative-quantitative analysis. Based on the analysis, the total occurrences of F-Words in the corpus is 7938 occurrences and showed that there is a variation of lexical equivalence of F-Words translation in Indonesia. The finding reveals that the lexical translation of the F-Words in Indonesian is not restricted to negative or taboo. Furthermore, the analysis on the function of F-Words translation in Indonesian translation shows the flexibility of F-Words which can be employed to show solidarity, emphasis meaning, insult, emotion, failure, and misery